NUSAP1 influences the DNA damage response by controlling BRCA1 protein levels - Kotian, Shweta (Landes Bioscience, 2014)
NUSAP1 has been reported to function in mitotic spindle assembly, chromosome segregation, and regulation of cytokinesis. In this study, we find that NUSAP1 has hitherto unknown functions in the key BRCA1-regulated pathways of double strand DNA break repair and centrosome duplication. Both these pathways are important for maintenance of genomic stability, and any defects in these pathways can cause tumorigenesis. Depletion of NUSAP1 from cells led to the suppression of double strand DNA break repair via the homologous recombination and single-strand annealing pathways. The presence of NUSAP1 was also found to be important for the control of centrosome numbers. We have found evidence that NUSAP1 plays a role in these processes through regulation of BRCA1 protein levels, and BRCA1 overexpression from a plasmid mitigates the defective phenotypes seen upon NUSAP1 depletion. We found that after NUSAP1 depletion there is a decrease in BRCA1 recruitment to ionizing radiation-induced foci. Results from this study reveal a novel association between BRCA1 and NUSAP1 and suggests a mechanism whereby NUSAP1 is involved in carcinogenesis.